Intercropping and environmental seasonality modulate the physiology and growth of Hancornia speciosa (Gomes) - Estenio Moreira Alves; Fabiano Guimarães Silva; Roniel Geraldo Avila; Lucas Loram Lourenço; Thales Caetano de Oliveira; Aldo Max Custódio; Márcio Rosa; João Paulo Pennacchi; Tiago do Prado Paim (CABI Agriculture and Bioscience)
Abstract Background The recovery process of degraded areas with the implantation of orchards of native species is still little known. Thus, we intend to evaluate the physiological performance of Hancornia speciosa during different seasons of the year, cultivated in full sun and in intercropping for recovery of degraded areas. Methods Intercropping with Syagrus oleracea (double intercropping); with annual crops (double intercropping); and with S. oleracea and annual crops (triple intercropping) were completed over two years at the beginning of each season. Crops (experimental plots) were planted using a Nelder wheel design. Results Over the two years, H. speciosa was observed to experience seasonal regulatory changes, some of which were mitigated by the intercropping. The cultivation arrangement influenced the physiology and consequently the growth of H. speciosa. Conclusions It is concluded that the double intercropping benefits the growth of H. speciosa during the formation of the orchard, and the triple intercropping does not affect growth in relation to full sun. It is recommended the implantation of orchards of H. speciosa in recovery areas through intercropping.